Design of a 3.4‐MW wind turbine with integrated plasma actuator‐based load control. Issue 3 (30th September 2021) - Chetan, Mayank; Sakib, M. Sadman; Griffith, D. Todd; Gupta, Abhineet; Rotea, Mario A.
Abstract: Historically, cost reduction in wind energy has been accomplished by increasing hub heights and rotor diameters to capture more energy per turbine. The growth in rotor and turbine costs with increasing turbine sizes is also driven by the additional structure that must be added to withstand unsteady aerodynamic loads caused by turbulence, gusts, wind shear, misaligned yaw, upwind wakes, and the tower shadow. In this paper, we present a holistic design solution to integrate active load control using a controllable Gurney flap based on plasma actuators. We illustrate the design solution for a land‐based 3.4‐MW wind turbine rotor. Comparisons to a baseline reference 3.4‐MW wind turbine show significant load reduction (15–18% DEL reduction for flap‐wise blade root moments), rotor mass reduction (5–8%), and LCOE reduction (1.16–3.11%). To achieve these results, a comprehensive sequential‐iterative design procedure is introduced to integrate the controllable Gurney flap into the turbine design and to drive the design solution toward the best LCOE reduction solution. Results are presented for mapping fatigue load reductions into cost reductions. In addition, an evaluation of active load control extended from Region‐III to also include Region‐II showed a further 34% reduction in DEL.